Peran Majelis Taklim An-Nur dalam Pendidikan Kemandirian Perempuan di Desa Trenten - Nurul Afifah (Al Ghazali, 2023)
The majority of women are not aware of the rights they should have. Lack of self-confidence of women in showing their potential. Lack of awareness of the role of women in terms of independent behavior. Low knowledge related to the independence of women's behavior. So women are expected to have independence in dealing with all life's problems, assertive in the action of carrying out its role in the family and community environment and confident in applying their knowledge correctly through education at the Taklim Council. The research method used is with a phenomenological research approach. Research data collection is done in a way observation, interview, and documentation. The subject is the management and several members of the Taklim An-Nur Assembly. Women's Independence Education in Trenten Village through routine activities at the An-Nur Taklim Assembly that is weekly, monthly or annual activities. Through these activities women's self-reliance education appears in the behavioral aspect. Supporting factors for women's self-reliance education at the An-Nur Taklim Assembly, that is all Muslim communities, there is motivation from the taklim board of directors, get family support, get adequate infrastructure and there are speakers as well as very supportive environmental conditions. The inhibiting factor is lack of funds, lack of awareness from members, and the activities of each member. The implications of the role of the Taklim An-Nur Assembly on women's self-reliance education very good contribution. Because of the taklim assembly has a very big role for society, including in individual development. As well as women have self-confident, women are given the opportunity to be leaders in routine activities, women can participate in the management of women's bodies and women have fatigue in making a decision.